KRISTUS SEBAGAI JALAN PERDAMAIAN: TINJAUAN EKSEGETIS DAN TEOLOGIS TERHADAP EFESUS 2:14-18 DALAM KONTEKS PERSATUAN ETNIS - Edison, Edison Patalatu; Jeppri Nainggolan. (STT-RAI Batam, 2024)
This study aims to analyze Ephesians 2:14-18 with a focus on the theme of atonement presented by Christ in the context of the relationship between Jews and Gentiles. Through an exegetical approach, this study explores the meaning of the text in the historical and cultural context of the early church, as well as its implications for the theological understanding of ethnic unity in the body of Christ. Using text analysis methods, the study identified how Jesus' death on the cross served as a barrier breaker that separated the two groups, as well as opening access to God for all believers. The findings of this study show that the atonement achieved through Christ is not only spiritual but also social, which promotes the creation of an inclusive community within the church. This research contributes to a deeper understanding of Christ's role as a path of peace and its relevance in the context of today's multicultural society.